„Rozstępy” przyszłości: o trudnych powiązaniach technologii, kultury i natury - Marcin Jewdokimow; Barbara Markowska (Studia Ecologiae et Bioethicae, 2014)
Based on an interpretation of selected texts concerning ambient technology (AmI) the article critically discusses the relationship between technology, culture, and nature. A posthumanist approach to the analysis is adopted, allowing for the unveiling of the ruptures and splits related to such issues as subjectivity, culture-nature dichotomy, and technological development.